Effect of Silanol Groups on the Acidic and Catalytic Properties of Alkylsulphoacidic Silicas and SiO/Nafion Nanocomposites - Sergei A. Alekseev; V.N. Zaitsev; A.N. Alekseev; Yu.N. Kochkin; J. Evans (Adsorption Science & Technology)
Sets of silicas covalently modified with alkylsulphoacidic groups (SiO 2 -SO 3 H) and nanocomposites of silica with superacidic Nafion® polymer (SiO 2 /Nafion) were synthesised. End-capping the silanol groups with trimethylsilyl groups was used to obtain surface hydrophobisation. The materials obtained were characterised by nitrogen and water adsorption measurements, MAS NMR spectroscopy and dielectric relaxation spectroscopy (DRS). The acidity of the materials was tested by 31 P MAS NMR spectroscopic examination of samples with adsorbed triethylphosphine oxide (TEPO). It was demonstrated that end-capping excluded part of the surface silanol groups from interaction with acidic groups, thereby causing the sulphonic groups to exhibit an increased acidity. With SiO 2 -SO 3 H, end-capping also increased their catalytic activity in the synthesis of ethyl t-butyl ether (ETBE). However, end-capping had a negligible effect on the catalytic properties of SiO2/Nafion, probably because the catalytic reaction occurred inside the Nafion polymer nanoparticles.